Economic value of regular monitoring of response to treatment among US patients with chronic myeloid leukemia based on an economic model. (3rd October 2018) - Jabbour, Elias J.; Siegartel, Lisa R.; Lin, Jay; Lingohr-Smith, Melissa; Menges, Brandy; Makenbaeva, Dinara
Abstract: Background: Regular molecular monitoring with reverse-transcription quantitative PCR (RT-qPCR) analysis of BCR-ABL1 transcripts is associated with reduced disease progression among patients with chronic myeloid leukemia (CML). Molecular monitoring assists in the timely detection of primary or secondary resistance to tyrosine kinase inhibitor (TKI) therapy and is a recommended practice by the National Comprehensive Cancer Network guidelines. An economic model was developed to estimate the potential impact of CML monitoring vs lack of monitoring on patient healthcare costs. Methods: An Excel-based decision-analytic economic model was developed from a US payer perspective. The model was used to estimate the expected healthcare cost differences between regular molecular monitoring of CML patients and lack of monitoring. CML progression rates among patients with vs without monitoring, the annual cost of CML progression, the average number of monitoring tests per year, and the average cost per RT-qPCR monitoring test were incorporated into the model. Univariate and multivariable sensitivity analyses were conducted. Results: Based on estimates in published literature, disease progression to the accelerated/blast phase occurs among 0.35% of patients with monitoring and 5.12% of patients without monitoring, and the annual cost of CML progression is 136, 308 per patient year. The analysis found that total healthcare costs, including the costs associated with CML progression and RT-qPCR monitoring tests (three tests per year), were 1, 142 for patients with monitoring and 6, 982 for patients without monitoring (difference = 5, 840). In a hypothetical cohort of 100 patients with CML, achieving a 100% monitoring rate was associated with a total cost-savings of 584, 005 compared to a 0% monitoring rate. This cost-savings remained consistent under both univariate and multivariable sensitivity analyses. Conclusion: Regular CML monitoring was associated with improved outcomes among CML patients and, consequently, reduced healthcare costs.